AL-FEC for Streaming Services over LTE Systems - Christos Bouras; Andreas Papazois; Vasileios Kokkinos; Nikos Kanakis (14th International Symposiumon Wireless Personal Multimedia Communications, Brest, France, 2011)
The Third Generation Partnership Project (3GPP), recently introduced the evolution of the third generation (3G) cellular networks, the Long Term Evolution (LTE) telecommunication system. A key aspect of LTE specifications is the enhancement of Multimedia Broadcast/Multicast Services (MBMS), where the same content is transmitted to multiple users located in a specific service area. A significant point of the demanding multimedia services is the enhancement of the robustness against packet losses. To this direction, in order to support the efficient point-to-multipoint download and streaming delivery, 3GPP has included an Application Layer Forward Error Correction (AL-FEC) scheme in the MBMS standard. The standardized AL-FEC scheme is based on the systematic, fountain Raptor codes. In this paper, we investigate the application of AL-FEC over the MBMS streaming delivery method. We consider the benefits of AL-FEC for a seamless multimedia streaming transmission to multiple mobile users and we examine how the amount of FEC overhead can be adjusted under different packet loss conditions. For this purpose, we present a variety of realistic simulation scenarios for the performance evaluation of FEC considering several network and FEC encoding parameters. Furthermore, we provide suggestions in order to achieve efficient use of Raptor codes over LTE MBMS streaming services.
Keywords: FEC; LTE; MBMS